Edukasi Hak Perempuan Dan Persamaan Gender Dalam Hukum Di Angkatan Muda Ranting Solagratia Ambon - Salamor, Yonna Beatrix; Salamor, Anna Maria; Uneputty, Meidilin (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The study of women has been widely carried out in various disciplines from a biological, historical, and cultural perspective. This study of women began to emerge after the awareness of society, especially women, about their different views, status and roles compared to men. The fact that there are differences between women and men from various aspects has prompted activists to fight for change and efforts to eliminate the views that cause these differences, so that the differences between women and men are only due to biological differences.Purposes of the Research: The purpose of this article is to provide an overview of the view of women's rights in a small society and the emergence of gender inequality which can be one of the triggers for domestic violence (KDRT) in women.Methods: Community service activities carried out in the Solagratia Youth Force are a community service activity carried out in several stages, namely Identifying problems faced by cadres of AM GPM Subdistrict Solagratia, providing education about women's rights and gender equality for AM GPM Ranting Solagratia cadres . From the stages carried out, the method used in community service activities at AM GPM Ranting Solagratia is an educational method through legal counseling on women's rights and gender equality for AM GPM Ranting Solagratia cadres.Results / Findings / Novelty of the Research: After conducting identification based on data obtained from coordination with the executives of the Solagratia Subdistrict AM GPM, a community service activity was planned for January 30, 2021. After conducting educational activities on women's rights and gender equality through counseling given to all cadres of the Solagratia GPM Youth Force There are several facts that are quite surprising, including a lack of knowledge about the right to get the highest education without exception, so that it creates the mindset of both parents and members themselves who think it is important that women have graduated from high school in order to help the family economy by working and ignore the desire to continue education to a higher stage. Second, female cadre members often experience domestic violence as a result of marriage at a young age.